"Bringing the outside world in": Enriching social connection through health student placements in a teaching aged care facility. (11th April 2017) - Annear, Michael J.; Elliott, Kate‐Ellen J.; Tierney, Laura T.; Lea, Emma J.; Robinson, Andrew
Abstract: Background: Older adults living in residential aged care facilities (RACFs) often experience limited opportunities for social connection despite close proximity to peers, which has implications for mental health and quality of life (QoL). The introduction of large‐scale undergraduate health student placements in RACFs may enhance opportunities for meaningful engagement through social connection, although this remains unexplored. Objective: This research explores whether interpersonal encounters between health students and RACF residents influence residents' opportunities for social connection and QoL. Methods: A mixed methods design was employed which included questionnaire data from residents, and qualitative interview data from residents, family members and RACF staff. Data were collected during and after student placements to allow for an in‐depth exploration of residents, family members and staff perspectives. Results: Forty‐three participants (28 residents, 10 staff and five family members) were recruited during 2014. Overall, many residents had clinical levels of depression, mild cognitive impairment and multiple morbidities, however reported moderate‐to‐good QoL. Thematic analysis was undertaken on interview transcripts, and three themes emerged: (i) social isolation and loneliness fostered by residents' age‐related conditions, (ii) students expand socially supportive connections beyond the RACF and (iii) meaning making by sharing health experiences, which was found to help renegotiate older adults' pervasive narrative of vulnerability. Conclusion: Supported and structured health student placements in RACFs enable older adults to participate in meaningful encounters with younger people. These encounters focus on sharing health experiences and address long‐standing issues of isolation and loneliness by providing opportunities for social connection.